Determinants of Intention of Dentists for Providing Dental Care to HIV/AIDS-infected patients based on Protection Motivation Theory - Farbod Ebadifard-Azar; Tahereh Dehdari; Shila Laka; Laleh Dehdari; Arezoo Khanipour (Iranian Association of Health Education and Health Promotion, 2015)
Background and objective: Reluctance of dentists to treat HIV/AIDS patients represents a major concern.The present study was aimed to determine predictive factors of intention of dentists for providing dental care to HIV/AIDS-infected patients based on Protection Motivation Theory (PMT) constructs.  Methods: In this descriptive-analytical study, 80 dentists in the city of Shahriar, near Tehran, were selected through census. A scale based on PMT constructs was developed and validated through qualitative content analysis by a panel of experts and its reliability by Alpha Cronbach. Data was analyzed using SPSS16 and tests such as Pearson correlation, one-way ANOVA, independent-samples t tests and multiple linear regression using the stepwise method. Results: The mean age of participants was 38.21 (±7.57) years old 31 (38.8%) of the participants were women. Participants had an average of 117.98 (± 71.83) months of working experience. Among PMT constructs, self-efficacy could predict 54% variance of intention among the subjects (R2= 0.54, F= 24.28, p< 0.001) Conclusion: For increasing the intention of dentists willing to provide dental care to HIV/AIDS-infected patients should be focused on developing interventions aimed at to increase their self-efficacy. Paper Type: Research Article